Pemenuhan Hak Pendidikan Keolahragaan Bagi Anak yang Berkonflik dengan Hukum di Lembaga Pembinaan Khusus Anak Tangerang - Alvin Surya Pramana; Mitro Subroto (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2021)
The importance of education for children in life, it needs to be given to all children but what about children in conflict with the law who are serving their criminal period at the Special Children's Institution, education carried out by means of Packages A, B, and C is one solution but is it in the solution? Therefore, sports education is given and how the education is given. In this study, it is explained that sports education has been implemented with its programs in formal, non-formal and informal education. To obtain the results of research on the fulfillment of the right to Sports Education, this research uses qualitative research methods by means of observation and also conducts case studies of applicable laws. This study has a purpose, namely to find out and obtain data about the implementation of the fulfillment of the right to education for children in conflict with the law at the Special Child Development Institute, especially in Sports Education. Children who are in conflict with the law have the right to education. Sports Education is education that focuses on physical and sports which is carried out as part of a regular and continuous educational process and has the aim of obtaining physical fitness, personality, skills, health, and knowledge. Sports Education is one form of an implementation of coaching at the Special Child Development Institute. The limited facilities and infrastructure at the Child Special Guidance Institute do not become an obstacle to fulfilling the right to education for children, especially sports education. The results of this study indicate that the implementation of the fulfillment of the right to education, especially Sports Education, is carried out well even though in its implementation it is still not optimal in fulfilling the Right to Education for Children in the Special Guidance for Children Institutions because there are several factors from internal and external factors.